2009
DOI: 10.1111/j.1528-1167.2008.01736.x
|View full text |Cite
|
Sign up to set email alerts
|

Periictal diffusion abnormalities of the thalamus in partial status epilepticus

Abstract: SUMMARYPurpose: To identify and describe thalamic dysfunction in patients with temporal as well as extratemporal status epilepticus (SE) and to also analyze the specific clinical, radiological, and electroencephalography (EEG) characteristics of patients with acute thalamic involvement. Methods: We retrospectively identified patients who presented with clinical and electrographic evidence of partial SE and had thalamic abnormalities on diffusion-weighted imaging (DWI) within 5 days of documentation of lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 36 publications
(45 reference statements)
2
57
1
Order By: Relevance
“…Coexisting thalamic abnormalities in seizure patients are likely the result of excessive activity in the thalamic nuclei having reciprocal connections with the affected cerebral cortices (25)(26)(27). Therefore, the thalamus may be related to the evolution and propagation of ictal discharge (27). In agreement with previous results (2, 28), we observed hippocampal involvement in 10 patients (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Coexisting thalamic abnormalities in seizure patients are likely the result of excessive activity in the thalamic nuclei having reciprocal connections with the affected cerebral cortices (25)(26)(27). Therefore, the thalamus may be related to the evolution and propagation of ictal discharge (27). In agreement with previous results (2, 28), we observed hippocampal involvement in 10 patients (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…In previous studies, investigators have suggested that thalamic nuclei are involved in various epilepsy syndromes. Coexisting thalamic abnormalities in seizure patients are likely the result of excessive activity in the thalamic nuclei having reciprocal connections with the affected cerebral cortices (25)(26)(27). Therefore, the thalamus may be related to the evolution and propagation of ictal discharge (27).…”
Section: Discussionmentioning
confidence: 99%
“…3). The degree of ADC decrease has been found to correlate with neuronal cell loss in animal studies [29] and restricted diffusion has been seen in the hippocampal formation, cortex, and the posterior thalamus after SE [24,30,31] in humans. So far no studies investigated diffusion abnormalities of the IIC.…”
Section: Strategymentioning
confidence: 94%
“…These peri-ictal diffusion abnormalities of the thalamus, likely the result of excessive activity in the thalamic nuclei having reciprocal connections with the involved cortex, are associated with seizure origin in the posterior quadrant and with the presence of ipsilateral cortical laminar involvement on DWI [23]. …”
Section: Status Epilepticusmentioning
confidence: 99%